2014
DOI: 10.1111/jop.12260
|View full text |Cite
|
Sign up to set email alerts
|

Oral Candida carriage and prevalence of Candida species among Maras powder users and non‐users

Abstract: We found that a significantly high rate of the Maras powder users was Candida carriers. It should be kept in mind that opportunistic infections may be caused by Candida species in Maras powder users especially with immunosuppressive conditions since Candida species are likely to lead to such infections in cases of immunosuppressive diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…which are often reported at higher prevalence than C. dubliniensis [ 7 , 55 ], and among denture stomatitis patients, e.g. C. krusei and C. parapsilosis [ 56 , 61 ], or in oral samples in general, e.g. C. tropicalis [ 61 , 62 ], were not observed in this cohort.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…which are often reported at higher prevalence than C. dubliniensis [ 7 , 55 ], and among denture stomatitis patients, e.g. C. krusei and C. parapsilosis [ 56 , 61 ], or in oral samples in general, e.g. C. tropicalis [ 61 , 62 ], were not observed in this cohort.…”
Section: Resultsmentioning
confidence: 61%
“…C. krusei and C. parapsilosis [ 56 , 61 ], or in oral samples in general, e.g. C. tropicalis [ 61 , 62 ], were not observed in this cohort.…”
Section: Resultsmentioning
confidence: 68%
“…Many epidemiological studies have reported a close relationship between smoking and the occurrence of C. albicans infection. 2,3 A previous study reported that patients with clinically suspected oral leucoplakia (OLK) who had smoking habit were significantly associated with Candida infection. 4 We have previously shown that smoking exacerbates oral C. albicans infection and dampens the defence response of epithelial cells in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the carriage rate of oral Candida species in healthy subjects ranges between 17% and 75% (2,3). A significant risk factor for increased oral Candida carriage is habitual tobacco usage (cigarette smoking and tobacco chewing) (4,5). One possible reason for this is that chemicals in tobacco, such as nicotine, nitrosodietheinal amine and aromatic hydrocarbons, act as sources of nutrition for Candida species, thus facilitating their growth (6).…”
Section: Introductionmentioning
confidence: 99%